Tinjauan Yuridis terhadap Penetapan Dispensasi Kawin di Pengadilan Agama Lubuk Pakam : Studi Penetapan Nomor 46/Pdt.P/2024/PA.Lpk - Dian Anggraini Sihombing; Muhammad Hizbullah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
Marriage in Islam is not only a civil bond, but also a very strong bond (mitsaqan ghalidzan) to obey Allah's commands and carry it out as worship. The purpose of marriage in Islam is to fulfill religious guidance in order to establish a harmonious, prosperous and happy family, where the relationship between husband and wife is in a strong bond in accordance with the commands of Allah SWT. The purpose of this study is to analyze the legal provisions regarding marriage dispensation, analyze the judge's legal considerations in Decree Number 46 / Pdt.P / 2024 / PA.Lpk., and analyze the implementation of the principle of the best interests of children in determining marriage dispensation at the Lubuk Pakam Religious Court. The research method used is normative juridical legal research with a document study approach to laws and court decisions. Data sources consist of primary data obtained through interviews with judges, clerks, and religious figures, as well as secondary data in the form of primary, secondary, and tertiary legal materials. The data analysis technique uses qualitative analysis. The results of the study show that: Legal provisions regarding marriage dispensation are regulated in Article 7 of Law Number 16 of 2019 which sets the minimum age limit for marriage at 19 years for men and women, with exceptions where dispensation can be requested from the Court for urgent reasons. Supreme Court Regulation Number 5 of 2019 regulates the procedure for examining marriage dispensation cases which requires the judge to listen to the child's statement, verify the absence of coercion, and consider the best interests of the child. The judge's legal considerations in Decision Number 46/Pdt.P/2024/PA.Lpk. have fulfilled formal requirements by considering the authority to adjudicate, the applicant's legal standing, the reasons for the request in the form of a very close relationship, the absence of coercion, the absence of obstacles to marriage, and the economic readiness of the prospective husband. The implementation of the principle of the best interests of the child has been carried out through providing advice on the risks of child marriage, listening to the child's opinions, and suggesting marriage postponement, although there are still limitations such as the lack of referrals to psychologists and minimal consideration of continuing education. The conclusion of this study is that the Lubuk Pakam Religious Court has implemented the provisions of marriage dispensation in accordance with applicable laws and regulations. The judge's legal considerations in Decree Number 46/Pdt.P/2024/PA.Lpk have fulfilled the formal and material aspects, however, the implementation of the principle of the best interests of the child still faces challenges from the normative, institutional, and socio-cultural aspects.